Customer Satisfaction and Brand Loyalty: A Case Study of Nestlé - Daisy Mui Hung Kee; Zi Wei Gan; Yi Qi Chan; Hui Tian Lee; Xiang Yee Tan; Sin Wei Lee (Global Academia Publisher, 2021)
The paper aims to examine the customer satisfaction and brand loyalty of Nestlé. Nestlé is one of the world's largest food companies. The company believes in the power of food to enhance life. The mission of Nestlé is